2019
DOI: 10.3390/ma12213474
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Corrosion and Cell Response of Hydroxyapatite Coated Mg Matrix in Situ Composites for Biodegradable Material Applications

Abstract: In this study, hydroxyapatite (HAp) coated Mg matrix composites were fabricated for biodegradable implant applications. Spark plasma sintering was employed to fabricate the Mg-10 wt% ZnO composite substrates. HAp was coated on the surface of the sintered composites and pure Mg by a chemical solution treatment. SEM and optical micrographs of coated samples showed that HAp grew homogeneously and formed a layer on the entire surface of both pure sintered Mg and Mg composites. The immersion and polarization test r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…The uniform-crystalline structure of the HA coating grown at pH 7.5 created a wall to protect the substrate from the solution. However, as reported previously 15,22 that there are always nano-pores existed in HA layer formed on the surface of Mg alloys. Therefore, the corrosion still occurred for this sample with a very low rate.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The uniform-crystalline structure of the HA coating grown at pH 7.5 created a wall to protect the substrate from the solution. However, as reported previously 15,22 that there are always nano-pores existed in HA layer formed on the surface of Mg alloys. Therefore, the corrosion still occurred for this sample with a very low rate.…”
Section: Discussionsupporting
confidence: 63%
“…The formation of Mg(OH) 2 on the surface of sample coated at pH 10.5 was consistent with results of previous studies. 15,25 Cao et al and Lei et al reported that, at a high corrosion rate of Mg alloys, the corrosion product deposited on the surface of the sample was mainly Mg(OH) 2 . This Mg(OH) 2 layer has porous structure as shown.…”
Section: Discussionmentioning
confidence: 99%
“…Also, surgery cost is expensive and the cost cannot be ignored. To address these two points, magnesium and its alloys are widely mentioned as desirable materials for solving these problems [2,12,13]. The Young's modulus of cortical bone is known to be approximately 20 to 30 GPa.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the effects of the preparation method on the mechanical properties of Mg-HAP composites were even stronger than the volume fraction of reinforcement. Cao et al [13] coated Mg matrix composites with a HAP layer using a chemical solution treatment. They tested the in vitro corrosion behavior and cell response by immersion, polarization test, and cell culture tests.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation